Early dissociation between neural signatures of endogenous spatial attention and perceptual awareness during visual masking - Wyart, Valentin; Dehaene, Stanislas; Tallon-Baudry, Catherine (Frontiers in Human Neuroscience, 2012)
The relationship between spatial attention and conscious access has often been pictured as a single causal link: spatial attention would provide conscious access to weak stimuli by increasing their effective contrast during early visual processing. To test this hypothesis, we assessed whether the early attentional amplification of visual responses, around 100 ms following stimulus onset, had a decisive impact on conscious detection. We recorded magnetoencephalographic (MEG) signals while participants focused their attention toward or away from masked stimuli which were physically identical but consciously detected half of the time. Spatial attention increased the amplitude of early occipital responses identically for both detected and missed stimuli around 100 ms, and therefore did not control conscious access. Accordingly, spatial attention did not increase the proportion of detected stimuli. The earliest neuromagnetic correlate of conscious detection, around 120 ms over the contralateral temporal cortex, was independent from the locus of attention. This early activation combined objective information about stimulus presence and subjective information about stimulus visibility, and was followed by a late correlate of conscious reportability, from 220 ms over temporal and frontal cortex, which correlated exclusively with stimulus visibility. This widespread activation coincided in time with the reorienting of attention triggered by masks presented at the uncued location. This reorienting was stronger and occurred earlier when the masked stimulus was detected, suggesting that the conscious detection of a masked stimulus at an unexpected location captures spatial attention. Altogether, these results support a double dissociation between the neural signatures of endogenous spatial attention and perceptual awareness.